Energy Efficiency, Basic Architecture, Applications and Safety Measures of Vehicle to Infrastructure Technology (V2I) - Nandhakumar. T; Madhumita. R; R, Janani. S (Journal of Power Electronics and Devices, 2017)
The paper presents a start-up study and tests relating to the likelihood of using ZigBee communications for vehicle-to-infrastructure (V2I) communications. Such communications need less energy consumption, compared to alternative technologies and are suggested for dense urban areas, wherever the density of infrastructure instrumentation reaches higher levels and involves vital power consumption. A image for vehicle identification victimization ZigBee protocol is bestowed as an answer to check V2I communications in laboratory conditions.